Safety assessment of a new developed fruit juice product - mixed fruit Juice in experimental rats - Hassan, Hadijah; Hazali, Norazlanshah; Ibrahim, Muhammad; Suri, Roowi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The interest in dietary antioxidants which are mainly found in fruits, has prompted research in the field of commercial high antioxidant juice for healthy purposes. Fruits also are rich with antioxidants that help in reducing of degenerative diseases such as cancer, arthritis, cardiovascular disease and inflammation. Based on the health claims from the natural antioxidants, a new healthy juice called Mixed Fruit Juice (MFJ) has been developed by using three combinations of local fruits (soursop, mango and kasturi lime). In order to promote the commercial use of this product, the safety evaluation is needed to be carried out. The 28-days repeated toxicity test has been conducted in female and male rats for pre-clinical safety assessment prior to human study. There was no mortality observed when varying doses of the MFJ (5, 10 and 20%) administered to all rats. Hematological analysis showed no significant differences in most parameters examined. There were no significant changes observed in the liver and kidney functions tests of all treated-rats as compared to control normal rats. Furthermore, lipid profiles and blood glucose level were also within the normal range as noted in control rats. The present data demonstrate that the supplementation of MFJ did not produce adverse effects on the body system of experimental rats. This is the first documented report on the safety assessment of MFJ in rats.